Cloud-Based Accounting and Digital Transformation in Indonesian MSMEs: Emerging Trends and Strategic Implications - R. Ricky Agusiady; R. Rita Avianty (Integrated Journal of Business and Economics (IJBE), 2026)
This study conducts a systematic literature review (SLR) to examine emerging trends and strategic implications of cloud-based accounting (CBA) adoption among Indonesian micro, small, and medium enterprises (MSMEs). Guided by the PRISMA protocol, the review analyzes 25 documents, including peer-reviewed journal articles and policy reports, using thematic coding grounded in the Technology Acceptance Model (TAM) and Technology–Organization–Environment (TOE) framework. The findings reveal that CBA adoption is shaped by multi-level drivers: cognitive perceptions such as perceived usefulness and digital trust; organizational capacities including managerial support and system readiness; and external pressures such as regulatory mandates, infrastructure disparities, and state-led digitalization programs. Rather than a purely technical upgrade, CBA adoption reflects broader institutional and ecological transitions within Indonesia’s fragmented digital economy. The study highlights the need for context-sensitive, ecosystem-based policy approaches to accelerate inclusive digital transformation in the MSME sector. It offers evidence-based insights for policymakers and practitioners navigating the digital finance landscape.